Differential biotransformation ability may alter fish biodiversity in polluted waters - Marco E. Franco; Juliane Hollender; Kristin Schirmer (Environment International)
Divergence in the activity of biotransformation pathways could lead to species sensitivity differences to chemical stress. To explore this hypothesis, we evaluated the biotransformation capacity of five fish species representative of Swiss biodiversity assemblages across watercourses surrounded by different land use. We report interspecific differences regarding the presence and activity of major biotransformation pathways, such as the invasive pumpinkseed (Lepomis gibbosus) displaying micropollutant clearance between 3- and 7–fold higher than native species (e.g. Salmo trutta, Squalius cephalus) collected in the same areas. These differences were exacerbated by urban and agricultural influence, which increased biotransformation potential at the enzyme level by approximately 11-fold and micropollutant clearance by approximately 2-fold compared to fish from areas with minimal human influence. In the context of the chemical defensome, we argue that fish with low biotransformation activity carry a greater burden on chemical stress, making them less likely to cope with additional stressors and sustain their population in competition with species with a higher biotransformation capacity, thus causing alterations to biodiversity assemblages.